Quetiapine combined with amisulpride in schizophrenic patients with insufficient responses to quetiapine monotherapy - Englisch, Susanne Angelika; Enning, Frank; Großhans, Martin; Marquardt, Lars; Waltereit, Robert; Zink, Mathias (Clinical neuropharmacology, 2010)
Objectives: Treatment resistance often leads to combinations of second-generation antipsychotics. Well-designed trials evaluated add-on strategies involving clozapine, but also olanzapine and quetiapine (QTP) have pharmacodynamic properties that render supplementation with high-affinity antidopaminergic second-generation antipsychotics, for example, amisulpride (AMS), reasonable. - Methods: We report on 6 cases with partial response of psychotic positive symptoms to QTP despite sufficient dosage (mean, 783 mg/d) and serum levels (mean, 405 μg/L). Concomitant drug abuse and interfering pharmacological changes were excluded. - Results: The add-on of AMS in a mean dose of 466.7 mg/d (serum level, 132.1 μg/L) over a period of 8.3 weeks facilitated significant improvements of treatment-resistant psychotic symptoms. The Positive and Negative Syndrome Scale scores decreased from 94 to 54, whereas the Scale for the Assessment of Negative Symptoms and the Calgary Depression Scale for Schizophrenia significantly improved. Despite an increase in the mean body weight from 77.2 to 82.9 kg and an increase in prolactin levels from 43 to 163 μg/L, the observed general tolerance was good. - Conclusions: The combination of AMS with QTP might be a successful strategy in individuals only partially responsive to quetiapine, but risks and benefits should be further evaluated in controlled clinical trials.
Gesehen am 25.05.2023